2010
DOI: 10.1007/978-3-642-12020-6_70
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Resistance in Brinjal against Nematode (Meloidogyne Incognita) Using cry1Ab Gene from Bacillus Thuringiensis Berliner

Abstract: Transgenic brinjal plants (Solanum melongena cv. Co2) expressing cryIAb gene from Bacillus thuringiensis Berliner (Bt) were evolved by Agrobacterium-mediated transformation system. In the present study, 7 T 0 lines (P-Co2IAb-5, P-Co2IAb-9, P-Co2IAb-10, P-Co2IAb-12, P-Co2IAb-16, P-Co2IAb-17 and P-Co2IAb-22) harboring cryIAb gene were obtained. PCR and Southern blotting analyses proved the presence and integration of cryIAb in these lines. A polyclonal rabbit anti-CryIAb antiserum detected the expression of a 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Neidig et al (2011) found that bacterial secondary metabolites responsible for the suppression of plant pathogens strongly inhibited bacterivorous nematodes and thus likely contributed to the resistance of bacteria against predators in soil. Phap et al (2010) investigated the potential of CryIAb gene from B. thuringiensis Berliner in controlling the root-knot nematode, Meloido-gyne incognita. Xu et al (2010) Municipal-solid waste (MSW) composting has proved to be a safe and effective way to make full use of MSW resources and to divert organic-waste materials to soil amendment or fertilizer (Shiralipour et al, 1992;Moldes et al, 2007;Herrera et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Neidig et al (2011) found that bacterial secondary metabolites responsible for the suppression of plant pathogens strongly inhibited bacterivorous nematodes and thus likely contributed to the resistance of bacteria against predators in soil. Phap et al (2010) investigated the potential of CryIAb gene from B. thuringiensis Berliner in controlling the root-knot nematode, Meloido-gyne incognita. Xu et al (2010) Municipal-solid waste (MSW) composting has proved to be a safe and effective way to make full use of MSW resources and to divert organic-waste materials to soil amendment or fertilizer (Shiralipour et al, 1992;Moldes et al, 2007;Herrera et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…M. incognita ingested the toxic 54 KDA protein which resulted in a fourfold decrease in reproduction. Phap et al (2010) reported that Cry1Ab protein in transgenic brinjal resulted in a decrease in the number of galls, egg masses and number of eggs per egg mass. Bt cotton has been evaluated for its reaction to parasitic nematodes.…”
Section: Introductionmentioning
confidence: 99%